2019
DOI: 10.1002/adma.201902163
|View full text |Cite
|
Sign up to set email alerts
|

H/F‐Substitution‐Induced Homochirality for Designing High‐Tc Molecular Perovskite Ferroelectrics

Abstract: A ferroelectric with a high phase‐transition temperature (Tc) is an indispensable condition for practical applications. Over the past decades, both strain engineering and the isotope effect have been found to effectively improve the Tc within ferroelectric material systems. However, the former strategy seems to prefer working in inorganic ferroelectric thin films, while the latter is also limited to some certain systems, such as hydrogen‐bonded ferroelectrics. It is noted that a mono‐fluorinated molecule is ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
270
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(281 citation statements)
references
References 36 publications
11
270
0
Order By: Relevance
“…Zhang and co‐workers directly used the inherent structural defects of nanocarbons to produce atomically dispersed Co–N x –C active sites through defect engineering. The obtained catalyst presented a layered porous structure with Co–N x –C group, nitrogen doping, oxygen functional group and topological defects, and high‐density active sites, making both ORR and OER have significant dual‐functional electrocatalytic activity under alkaline conditions . In addition, many studies indicated that the coordination between heteroatoms and metal in carbon materials, especially FeCo–N x –C, can significantly alter the electronic structure, so as to optimize the intermediate adsorption, thus showing better activity than noble metal catalysts .…”
Section: Defective Electrode Materials For Rechargeable Batteriesmentioning
confidence: 99%
“…Zhang and co‐workers directly used the inherent structural defects of nanocarbons to produce atomically dispersed Co–N x –C active sites through defect engineering. The obtained catalyst presented a layered porous structure with Co–N x –C group, nitrogen doping, oxygen functional group and topological defects, and high‐density active sites, making both ORR and OER have significant dual‐functional electrocatalytic activity under alkaline conditions . In addition, many studies indicated that the coordination between heteroatoms and metal in carbon materials, especially FeCo–N x –C, can significantly alter the electronic structure, so as to optimize the intermediate adsorption, thus showing better activity than noble metal catalysts .…”
Section: Defective Electrode Materials For Rechargeable Batteriesmentioning
confidence: 99%
“…The XPS peak of CN in the NC@SA‐Co evidently shifts to a higher binding energy compared with that in NC. The result could be attributed to the binding of Co with N in the moieties of CoN x C, which is consistent with the results reported by other works . The element valence state of the single Co atom in the NC@SA‐Co was also investigated in detail using the XPS.…”
Section: Resultsmentioning
confidence: 51%
“…N 1s spectrum for CoNC reveals the coexistence of pyridinic (398.4 eV), pyrrolic (400.5 eV), graphitic (401.4 eV), oxidized (403.0 eV), and chemisorbed (405.2 eV) nitrogen species (Figure d). Compared with NGM (Figure S3f, Supporting Information), a new peak at 399.3 eV can be assigned to the N coordinated with Co, manifesting the presence of CoN x species . These results strongly indicate a high dispersion of single Co atoms in the porous CoNC layers with CoN x C configurations, which can potentially realize uniform deposition of Li metal.…”
mentioning
confidence: 86%